Regulatory Sandbox dan Implementasi pada Inovasi berbasis Financial Technology (Fintech) - Indri, Indri Syahfitri (Journal of Law and Administrative Science, 2024)
Abstract. The development of financial innovation called "Financial Technology" has developed rapidly so far. Disruption to digital finance certainly needs to be regulated in such a way as to minimize risk and stabilize the state financial system. In an effort to regulate this innovation, regulators place limits on digital forms of finance that are widely used by the public. Today's society tends to have an instant, easy lifestyle, and use online transactions. In this era, digital finance is at the top of society, one of the most forms of fintech is application-based lending that brings together lenders and recipients/borrowers in one application. With digital financial innovation getting fast attention from competitors in the business world outside of banks, they tend to take advantage of the community and namely the rise of online loans. One of the efforts to mitigate risk by financial institutions is to issue a Regulatory Sandbox policy through Bank Indonesia Regulation Number PBI No.19/12/PBI/2017 of 2017 concerning the Implementation of Financial Technology and Financial Services Authority Regulation (POJK) Number 13/POJK.02/ 2018 of 2018 concerning Digital Financial Innovation in the Financial Services Sector (POJK 13/2018). This study intends to analyze the extent to which these regulatory issues have represented the needs of agencies and society. This legal research uses empirical legal research methods, which this research relies on applicable laws and regulations as well as other related literature. The results of this research are the ineffectiveness of current regulations among the public and regulators as well as the increasingly complex problems faced by financial institutions, especially in the field of banking.